Techno-economical evaluation of an e-fuel-producing wind farm system focusing on hydrogen, ammonia and methanol production - Jönsson Lindholm, Carl (My University, 2023)
Given that the share of renewable energy sources will increase in future energy systems, coupling e-fuel production plants with intermittent electricity will be bene ficial. This study evaluates the techno-economical feasibility of hydrogen, ammonia and methanol production using electricity produced from a connected wind farm. A model was developed to also include grid interactions and the possibility to utilize batteries and fuel cells. Different cases and scenarios were assumed, and technical behaviours along with the profitability of investments were evaluated. Furthermore, an understanding of the power-to-x concept and its associated investment strategies was developed to display trends and behaviours in the system. The results of this study are however limited to some extent. Technical dynamics such as ramping times and hot standby of for example the ammonia and methanol production, were restrained by an hourly resolution together with software limitations. It was seen that peak-load shifting using batteries could increase profits and that a battery investment was beneficial seen to the additional amount of electricity sup plied to the grid. Using fuel cells and electrolyzers did not increase profits but could still pose a viable option in a scenario where the utilized wind energy has to be maximized. Regardless, batteries were seen to decrease profits when utilized to support hydrogen production, in spite of the fact that hydrogen production was in creased. Electricity prices and grid transfer capacities were seen to have a significant impact on the system which led to them being key parameters utilized to nuance the results. System configurations that maximized the profit could be found for the different cases, and results point toward ammonia likely being the most profitable option, even if methanol offers a more flexible synthesis with the hot-standby option. The main takeaway, however, is that the profitability of an e-fuel-producing energy system is significantly affected by the e-fuel market prices. For example, ammonia production was seen to give the highest profits, in the scenario with a market price of 1,000-1,500 €/tonNH3 , at around 3,000 M€ over the 20-year lifetime. Hydro gen could also compete with ammonia at a price of 5.5 €/kgH2 , and had a higher profitability when the ammonia price went below 1,500 €/tonNH3 at 1,500 M€.
Keywords: power-to-x; electrolysis; electrofuels; power-to-fuels; PTX; synthetic fuels; energy storage system; cost; profit